2008
DOI: 10.1038/sj.ijo.0803798
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of childhood obesity to adult carotid intima-media thickness: the Bogalusa Heart Study

Abstract: Objective: Although obese children are at increased risk for coronary heart disease in later life, it is not clear if the association results from the persistence of childhood obesity into adulthood. We examined the relation of both childhood and adult levels of body mass index (BMI, kg m À2 ) to carotid intima-media thickness (IMT) measured at the (mean) age of 36 years. Design and Subjects: Prior to the determination of adult IMT, the 1142 participants had been examined 7 (mean) times in the Bogalusa Heart S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(161 citation statements)
references
References 38 publications
7
135
0
13
Order By: Relevance
“…8,25,28,30,31 However, after adjusting for adult BMI only the cumulative change in BMI from one study 31 remained significant. An additional two studies showed positive associations with some age groups but not others.…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 89%
See 2 more Smart Citations
“…8,25,28,30,31 However, after adjusting for adult BMI only the cumulative change in BMI from one study 31 remained significant. An additional two studies showed positive associations with some age groups but not others.…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 89%
“…However, these differences became nonsignificant once adjusted for adult BMI. The final study 7 showed no significant correlations, either before or after 21 + 2 + **** * ** Freedman et al 32 + -*** * ** Hardy et al 23 + 2 -+ *** ** ** Lauer and Clarke, 10 + Not adjusted *** ** Li et al 33 + -*** * *** Sinaiko et al 9 + Not adjusted *** ** Wright et al 7 2 2 -*** * *** Carotid intima-media thickness Freedman et al 8 + 2 + 2 *** * ** Freedman et al 31 + Not all adjusted *** *** Juonala et al 25 + 2 2 *** * ** Oren et al 30 + 2 *** * ** Raitakari et al 28 + 2 *** * ** Wright et al 7 2 2 *** * ***…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies considered the association between childhood BMI and carotid intima media thickness (CIMT) (30,(35)(36)(37)(38)(39) , with five of these studies showing a positive association (35)(36)(37)(38)(39) . However, after adjusting for adult BMI only one positive association remained, and this was for the cumulative change in BMI from childhood to adulthood (39) . It must be noted that these studies assessed CIMT at a relatively young age in adulthood, so may be limited in their ability to determine the long-term risk associated with childhood obesity.…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…4 Furthermore, childhood body mass index levels tracked into adulthood and were related to adult carotid intima-media thickness, a marker of generalized atherosclerosis. 5 Clearly, diet is a major contributor to energy imbalance and therefore a key driver for both obesity and diet-related chronic disease risk, including cardiovascular disease, type 2 diabetes, some cases of type 1 diabetes and many cancers. 6 However, a solid evidence base of studies articulating the contribution of specific dietary intake patterns and food behaviors to effective prevention 7 and treatment 8 of childhood obesity and its sequelae is lacking.…”
Section: Introductionmentioning
confidence: 99%